pH-Responsive Pullulan Based Adsorbent Functionalized by Poly(N-vinylimidazole): Synthesis, Characterization and Dye Removal Application - Hezarkhani, Marjan; Usturk, Selma; Ozbilenler, Cahit; Yilmaz, Elvan (Pleiades Publishing Ltd, 2024)
In this study, a pullulan hydrogel is grafted by poly(N-vinylimidazole) (PNVI) in a heterogeneous acidic medium under a nitrogen atmosphere for Methyl Orange (MO) and Acid Green 25 (AG25) dye removal application. The effect of monomer concentration as a significant parameter for grafting yield is investigated thoroughly, and it is demonstrated that 189% grafting yield of PNVI grafted onto epichlorohydrin crosslinked pullulan (pullulan-ECH-graft-PNVI) can be obtained under proper conditions. Equilibrium water absorption capacity values reveal the pH-responsivity of pullulan-ECH-graft-PNVI hydrogels (6000%) as compared to the epichlorohydrin crosslinked pullulan (pullulan-ECH) hydrogel (1000%) counterpart. Further characterization of the samples was performed by Fourier-transform infrared (FTIR) spectroscopy, thermogravimetric analysis (TGA), and X-ray diffraction (XRD). Adsorption of MO and AG25 on pullulan-ECH-graft-PNVI samples was studied at various pH, dye concentration, and time. The optimal adsorption pH value was measured at pH 3.0 with an adsorption capacity of 36.6 mg MO/g adsorbent and 5.72 mg AG25/g adsorbent. Isotherms and kinetic studies describe the adsorption profiles of the samples. The adsorption trends of the samples best fit the Freundlich model, which supports heterolayer dye adsorption and surface heterogeneity. Adsorption kinetic results indicate a pseudo-second-order kinetic model, which shows chemisorption.
Keywords: pullulan; N-vinyl imidazole; graft copolymerization; hydrogel; dye adsorption